Quinto Império: Da ruptura à convergência das ordens suprassensíveis e sensíveis em Antônio Vieira - Oliveira, Victor Nojosa de (2023)
The present work aims to point out the concept of Fifth Empire in Antônio Vieira as the only promoting instance capable of establishing in the cosmos the full unity between the sensitive and suprasensible world. The cosmic balance had been fractured by the intrusion of original sin and the process of renewing totality will comprise the transformation of temporalities in accordance with the Providence of the divine Being without prejudice to the exercise of human freedom, since human beings are integrated into the divine Being in a relationship of reciprocal correspondence. The expansion of restoration will also bring together the natural, social and political dimensions. In this sense, the Fifth Empire is conceived as a paradigm present on the horizon of expectation and impels the human subject towards the permanent and uninterrupted flow of becoming. We seek, therefore, to understand that the Fifth Empire will promote the ontological fusion of all things in the divine Being. Therefore, the methodological option of this investigation is based on exegetical interpretations of central issues present in several of Vieira's works, as our research favors a thematic locus and does not center its analyzes on a specific work. We also carried out a bibliographical review of expert commentators on the thought of Father Antônio Vieira who certainly shed hermeneutical light on several intriguing questions. We conclude that the expansion of the restoration that will be ordered by the establishment of the fifth monarchy will also bring together the natural, social and political dimensions.